An evaluation of demographic and sociocultural factors affiliated with cooperative artiodactyl hunting in the prehistoric Great Basin, USA. Issue 4 (1st November 2018) - Sprengeler, Kari; Morgan, Christopher
Abstract : This research evaluates the association of ethnographically derived demographic and sociocultural variables with a large sample of communal, landscapescale hunting features (drivelines, corrals and traps) from across the Great Basin; it does so in an attempt to identify the sociocultural contexts that may have encouraged or discouraged people to cooperate rather than compete or operate individually. Results indicate that communal hunting was associated with moderate population densities and with greater degrees of ritual and some forms of property ownership, but not with greater degrees of leadership or territoriality. The implications of this work are that high population densities and entrenched leadership positions are not necessarily required for large-scale cooperative efforts and that territoriality may have retarded cooperation at the scales required to elicit large-scale group effort, at least in regions with relatively low population densities. It also appears that ritual may have played a role in generating the coherence necessary for cooperation among oftentimes far-flung, autonomous families and that privatising communal hunting features was necessary to underwrite the technological investment entailed by making and using these features.